Growth Performance of Broiler Chickens Fed a Carboxymethyl Cellulose Containing Diet with Supplemental Carvacrol and/or Cinnamaldehyde - Lee, K.-W.; Everts, H.; Kappert, H.J.; Beynen, A.C. (International Journal of Poultry Science, 2004)
The question addressed was whether the essential oil components, carvacrol and cinnamaldehyde, would have an interactive effect with regard to growth performance. One-day old female broiler chickens were subjected to one of 5 dietary treatments for 21 days: a base diet as a negative control, the base diet with 1% Carboxymethyl cellulose (CMC), the CMC diet with 200 ppm carvacrol, the CMC diet with 200 ppm cinnamaldehyde and the CMC diet with 100 ppm carvacrol plus 100 ppm cinnamaldehyde. Group mean daily weight gain was 10% less in birds fed on the CMC diet when compared with those fed the CMC-free diet. Birds fed the CMC-containing diet with the blend of carvacrol and cinnamaldehyde gained significantly less weight when compared with those fed on the CMC-free diet, the decrease in weight gain being 24%. The feeding of either carvacrol or cinnamaldehyde alone with the CMC-containing diet did not influence weight gain as opposed to the CMC control diet, but the combination of the two principles reduced group mean weight gain by 16%. The feeding of CMC caused hypertrophy of the small intestine, but the essential oil components had no further effect. No significant treatment differences were observed as to plasma lipid concentrations. The present data indicate that essential oil components can have interactive effects with respect to growth performance.